Perkembangan Usia Dini (Masa Kanak-Kanak Awal) - Yeti Murniati; Tya Ariani; Siti Aisyah; Linda Yarni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Early age is the initial phase of a child's development which will determine development in the next phase. Child development in the early phase is divided into 4 aspects of functional abilities, namely gross motor skills, fine motor skills and vision, speech and language, and social emotions and behavior.  If there is a deficiency in one aspect of this ability, it can affect the development of other aspects.  This research uses a critical review method, which involves careful examination and evaluation of various sources of information, such as scientific journals, articles and other media.  The main goal of this approach is to improve the reader's understanding and interpretation skills in the context of early childhood development, as well as offering a critical assessment of the material reviewed.  In addition, a critical review requires identifying important topics in the literature, analyzing the methodology used, and evaluating the strengths and limitations of the sources studied.  Socialization development is the development needed in training children's socialization of their environment. Cognitive development in early childhood is called the pre-operational stage.  At this stage stable concepts are formed, mental reasoning appears, egocentrism begins to strengthen, and belief in magical things is formed. According to Jean Piaget, moral development, early childhood is characterized by 'morality through coercion'.